Research on feeding path planning algorithm of bending robot based on improved artificial potential field method - Huang, Zhuoran; Ding, Dawei; Xu, Shuai; Xu, Fengyu (Chinese Control Conference, 2022)
In order to solve the problems of low efficiency and high collision probabilities of traditional bending, the collision between the sheet metal parts and the bending machine cannot be ignored upon establishing a coordinate system. Considering the factors such as pose calculation when moving parts, an improved Artificial Potential Field method based on discrete geometric calculation of main and auxiliary points is proposed for the shape characteristics of sheet metal parts. The potential field path controls the motion path of the sheet metal part and finds a collision-free bending robot working path. Finally, the improved method is simulated, and the results show that the algorithm can successfully guarantee no collision between the sheet metal part and the bending mechanism, and ensure that the robotic arm runs smoothly to the target position.